If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6+4x=3+8x-9
We move all terms to the left:
-6+4x-(3+8x-9)=0
We add all the numbers together, and all the variables
4x-(8x-6)-6=0
We get rid of parentheses
4x-8x+6-6=0
We add all the numbers together, and all the variables
-4x=0
x=0/-4
x=0
| -4+3x=2+2x | | 5^2x+3*5^x+1=100 | | -8.34-12d=-11.4d | | 1/8(8x-7)=-1/7-8/7 | | -9=6x+7-2x | | -4x-2(2x+10)=-160 | | 3(b–4)+5b=44 | | -(x-2)+3x=14 | | 8+6a=-6+8a | | 3(r+4)-2r=-5 | | f(3)=2(3)(6)-4(3) | | 18x-9=4x+5 | | v+4/5=9/5 | | 4x-2x+7=-21 | | 4-10x=44 | | 11x+15=6x+70 | | 447+x=−261 | | 15+4h=3+6h | | -3-4n=1-6n | | 9+2m-5-3=5m-5 | | 192=44-x | | y/3=1/21 | | 46=5x+3(x+2) | | a÷-2+9=30 | | b/2-5=6 | | 5+5u=6u-4 | | 16j+18=-20-10+20j | | 2u-1=-9-2u | | 13b+19=12b | | 2x+18x-10=47 | | 6-2j=10 | | x+3,000=21,000 |